Pengaruh Kombinasi Pemberian Aromatherapy Dan Guided Imagery Terhadap Kualitas Tidur Pada Pasien Penyakit Jantung Koroner - Elyana Fathur Rizki; Indah Sri Wahyuningsih; Retno Setyawati (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examined the effect of a combined aromatherapy and guided imagery intervention on sleep quality among patients with coronary heart disease. A quasi-experimental one group pretest–posttest design was conducted in a cardiac care setting with eighteen participants selected using purposive sampling. Sleep quality was measured using a standardized instrument before and after the intervention. Data analysis employed the Wilcoxon Signed Rank Test due to non-normal data distribution. The results demonstrated a statistically significant improvement in sleep quality following the intervention, indicating that the combination therapy effectively enhanced patients’ sleep patterns. Aromatherapy lavender contributed to autonomic relaxation, while guided imagery facilitated psychological calmness and emotional regulation, producing a synergistic effect. These findings align with previous evidence supporting complementary nursing interventions for cardiovascular patients. Improved sleep quality may support cardiovascular stability and overall recovery. The study concludes that combining aromatherapy and guided imagery represents a safe, feasible, and effective nonpharmacological nursing intervention to improve sleep quality in coronary heart disease patients and may be integrated into holistic nursing care practice settings